2002
DOI: 10.1111/j.1348-0421.2002.tb02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Human Gut Microbiota Using 16S rDNA Clone Libraries and Strictly Anaerobic Culture‐Based Methods

Abstract: The human gut microbiota from three healthy subjects were compared by the use of a sequence analysis of 16S rDNA libraries and a culture‐based method. Direct counts ranged from 1.9 × 1011 to 4.0 × 1011 cells/g (wet weight), and plate counts totaled 6.6 × 1010 to 1.2 × 1011 CFU/g (wet weight). Sixty to seventy percent of the bacteria in the human intestinal tract cannot be cultured with currently available methods. The 16S rDNA libraries from three subjects were generated from total community DNA in the intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
318
3
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(346 citation statements)
references
References 42 publications
11
318
3
5
Order By: Relevance
“…Suau et al (1999) sequenced and characterised 284 clones of 16S rRNA genes from a single human faecal sample, finding 82 species, many (76%) of which had previously been unknown. Hayashi et al (2002) analysed 744 clones from three subjects and came to similar conclusions, namely that there were about 130 species of which 75% were unknown. More recently, the true diversity of the bacterial flora of the human intestine has become much clearer, the result of a much larger cloning and sequencing study on three human volunteers (Eckburg et al, 2005).…”
Section: Microbial Diversity In the Human Intestine And The Rumenmentioning
confidence: 73%
See 1 more Smart Citation
“…Suau et al (1999) sequenced and characterised 284 clones of 16S rRNA genes from a single human faecal sample, finding 82 species, many (76%) of which had previously been unknown. Hayashi et al (2002) analysed 744 clones from three subjects and came to similar conclusions, namely that there were about 130 species of which 75% were unknown. More recently, the true diversity of the bacterial flora of the human intestine has become much clearer, the result of a much larger cloning and sequencing study on three human volunteers (Eckburg et al, 2005).…”
Section: Microbial Diversity In the Human Intestine And The Rumenmentioning
confidence: 73%
“…Figure 1 illustrates the persistence within individuals of the Bacteroidetes. Other studies had demonstrated the principle that different individuals had very different flora composition (Zoetendal et al, 1998;Suau et al, 1999;Tannock et al, 2000;Hayashi et al, 2002). There is, as some of the studies illustrate, a temporal persistence as well.…”
Section: Microbial Diversity In the Human Intestine And The Rumenmentioning
confidence: 94%
“…'Universal' primers for the gene make it possible simultaneously to amplify the genetic regions of mixtures of bacteria, including clusters of yet-tobe-cultured microbial species. Such unidentified species are known as phylotypes (Frank et al, 2003;Hayashi et al, 2002;Zhou et al, 2004), operational taxonomic units (OTUs) (Suau et al, 1999) and species-level operational taxonomic units (SLOTUs) (Pei et al, 2004). The current study was designed to determine the human skin microbiota by the The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA gene sequences of novel phylotypes (phylotypes A-M) are AB161079-AB161091.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-independent analyses of 16S rDNA libraries reveal that only 30% of the fecal flora appears cultivable, and there is significant variation in the flora in different gastrointestinal segments and luminal contents versus the mucosa of healthy individuals [23][24][25]. Analysis of 16S…”
mentioning
confidence: 99%